New Approach for the On-Line Spectrophotometric Determination of Folic Acid in Pure and Pharmaceutical Preparation via Oxidation by Cerium(IV) Sulphate Using Ayah 3Sx3-3D-Solar Cell CFI Spectrophotometer Analyzer - Jasim, Aktham N. (Iraqi Journal of Science, 2023)
A newly photometric analytical method characterized by its speed and sensitivity was developed for the determination of folic acid in pure and pharmaceutical samples via its oxidation to reddish-orange coloured complex through oxidation by cerium (IV) sulphate in aqua medium using homemade Ayah 3Sx3-3D-solar cell CFI photometer. The colored species were determined using supper bright green light emitting diode (LED) as a source. A 100μl was taken as a best sample volume for the determination of folic acid. The linearity of calibration curve for the instrument response versus folic acid concentration was 0.005-20 mmol.L-1 while the L.O.D. was 0.5  mol.L-1 from the stepwise dilution for the minimum concentration of lowest concentration in the linear dynamic range of the calibration graph. The correlation coefficient (r) was 0.9994 while the percentage linearity (r2%) was 99.88%. The method was applied successfully for the determination of folic acid in pharmaceutical preparation. RSD% for 8 mmo.L-1 (n=6) less than 1% . Using paired t-test it was shown that there was no significant difference between the proposed method and official method (Quoted value- 5mg) and on that basis the new method can be accepted as an alternative analytical method.